Flypaper Effect Pada Dana Alokasi Umum (DAU) Dan Pendapatan Asli Daerah (PAD) Terhadap Belanja Daerah Pada Pemerintah( Studi Pada Pemerintah Daerah Kabupaten/Kota Di Provinsi Lampung ) - Kurniawan, Widi Angga; , Drs. Suyatmim Waskito Adi, M.Si (2016)
This study aims to to investigate the possibility of flypaper effect on regional spending in government lampung provincial. The independent variable used is General Allocation Fund (DAU) and Local Revenue (PAD) and that which is dependent variable is Regionall Expenditure (BD). The purpose of this research is to give evidence empirical whether General Allocation Fund and the Local Revenue of its effect on regional expenditure of districts in Lampung Provincial Population in this research is the districts / cities in the lampung provincial in the period starting from 2011-2013 , whit amount sample 14 districts. This research was using a purposive sampling method. The data which is analyzed in this research are collected through the region budget of Revenue and Expence (APBD). The analytical tool used is multiple linear regression analysis. Based on the results of tests carried out in the period 3 (three years) between starting from 2011-2013 it can be seen that. General allocation Funds and the local revenue in together having influence a significant impact on regional spending. Variable general allocation funds more influential in significant impact on regional spending compared with local revenue. Prove the flypaper effect in response local government to DAU and PAD. Flypaper effect equally happened to the areas having local revenue low and with local revenue high.